Trainers in Didactic of Sciences and Mathematics: The Inter-Institutional Collaborative Self-Study as an Engine of Transformation of University Teaching - Hernandez-Silva, C; Vanegas-Ortega, C (ORGANIZACION ESTADOS IBEROAMERICANOS EDUCACION CIENCIA & CULTURA-OEI, 2020)
Within the framework of the professional challenges posed by university teaching today, in this article we characterize the reflexive processes that we live as didactics of experimental sciences and mathematics, when we develop an inter-institutional collaborative self-study. For this, we have adapted the Deweynian cycle according to two reflexive processes: the first, of self-confrontation about what happens in our university classes in contrast to the points made by students using tickets out, and the second, of resignification of university teaching with critics friends. The results show that each didact underwent different processes of reflection regarding the dimensions related to the students, the context, the specific teaching and professionalism. In addition, we demonstrate that didactic knowledge allows the configuration of differentiating reflective and identity processes that are key in the understanding and resignification of pedagogical practices.